Service use, clinical outcomes and user experience associated with urgent care services that use telephone-based digital triage: a systematic review. Issue 1 (3rd January 2022) - Sexton, Vanashree; Dale, Jeremy; Bryce, Carol; Barry, James; Sellers, Elizabeth; Atherton, Helen
Abstract : Objective: To evaluate service use, clinical outcomes and user experience related to telephone-based digital triage in urgent care. Design: Systematic review and narrative synthesis. Data sources: Medline, Embase, CINAHL, Web of Science and Scopus were searched for literature published between 1 March 2000 and 1 April 2020. Eligibility criteria for selecting studies: Studies of any design investigating patterns of triage advice, wider service use, clinical outcomes and user experience relating to telephone based digital triage in urgent care. Data extraction and synthesis: Two reviewers extracted data and conducted quality assessments using the mixed methods appraisal tool. Narrative synthesis was used to analyse findings. Results: Thirty-one studies were included, with the majority being UK based; most investigated nurse-led digital triage (n=26). Eight evaluated the impact on wider healthcare service use following digital triage implementation, typically reporting reduction or no change in service use. Six investigated patient level service use, showing mixed findings relating to patients' adherence with triage advice. Evaluation of clinical outcomes was limited. Four studies reported on hospitalisation rates of digitally triaged patients and highlighted potential triage errors where patients appeared to have not been given sufficiently high urgency advice. Overall, service users reported high levels of satisfaction, in studies of both clinician and non-clinician led digital triage, but with some dissatisfaction over the relevance and number of triage questions. Conclusions: Further research is needed into patient level service use, including patients' adherence with triage advice and how this influences subsequent use of services. Further evaluation of clinical outcomes using larger datasets and comparison of different digital triage systems is needed to explore consistency and safety. The safety and effectiveness of non-clinician led digital triage also needs evaluation. Such evidence should contribute to improvement of digital triage tools and service delivery. PROSPERO registration number: CRD42020178500.